The 5[prime] Flanking Regions of Vicilin and Napin Storage Protein Genes Are Down-Regulated by Desiccation in Transgenic Tobacco. - Jiang, L. (1995)
Drying of seeds, when imposed prematurely, elicits a switch in metabolism; events unique to development, such as synthesis of storage protein, are terminated, whereas syntheses associated with germination and growth are initiated. To determine the role of desiccation in down-regulating the expression of genes for storage proteins, the desiccation responsiveness of the 5[prime] and 3[prime] regulatory regions of the genes encoding the pea storage protein vicilin and the Brassica napus storage protein napin was tested in transgenic tobacco seed. Chimeric genes were introduced into tobacco; these genes consisted of the coding region of the reporter gene for [beta]-glucuronidase (GUS) and 5[prime] and/or 3[prime] regions from the vicilin or napin genes or, as controls, the same regions derived from constitutively expressed genes, presumed to be desiccation insensitive. In transgenic seed expressing the gene constructs containing the vicilin or napin promoters, GUS activities declined during late seed development, and more dramatically, after imbibition of mature dry seed or prematurely dried seed. In contrast, GUS activities increased after seed rehydration when the constitutive viral promoter replaced the storage-protein gene 5[prime] region. Transient expression assays support the hypothesis that premature drying down-regulates the expression of the storage-protein gene promoter. Following desiccation, this region may become insensitive to positive controlling factors; alternatively, changes to trans-acting factors may occur.